Flexible Distribution of Existing Web Interfaces: An Architecture Involving Developers and End-Users - Firmenich, Sergio Damián (2016)
This paper presents a novel approach towards the opportunistic and lightweight distribution of existent Web User Interfaces. We describe an architecture that allows end-users to collect UI objects into a distributed UI-Component-oriented PIM, accessible from different user’s devices. Once in the PIM, the collected UI components are wrapped with different DUI-based behaviours that may be triggered by the user, as PIM’s objects plug-ins. We present an overview of the architecture; some default DUI-based behaviours are introduced and illustrated through examples. Besides, we show how the architecture supports the development of new DUI-based behaviours.